Stature prediction from phalangeal anthropometrics in north Karnataka population; India - Samreen Panjakash; Amjad Dastageer Mirzanaik; Irfan M. Itagi (Al Ameen Medical College, 2021)
Background: Stature is an important indicator in determining personal identification of an individual. Identification of the deceased has a pivotal role in various medicolegal cases. Attempts have been made by various researchers across the globe to correlate stature with various body parts. But relatively less attention has been given on correlating stature with the phalangeal length. Objectives: In the present study an attempt is made to correlate stature and phalangeal lengths of both the hands in males and females separately. Linear regression formulae are also derived to estimate stature of an individual from phalangeal lengths. Methods: 300 healthy individuals consisting of 150 males and 150 females belonging to North Karnataka population are selected. Stature is measured using Standard Stadiometer. Phalangeal lengths are measured using Vernier Callipers. Result: In present study, the proximal and middle phalangeal lengths of fourth digit (D4P; r=0.47, p=0.001) (D4M; r=0.47, p=0.001) showed higher correlation coefficient with stature in males. Among females, the proximal and distal phalangeal length of first digit of right hand showed highest correlation coefficient value and is significantly correlated with stature(D1P; r=0.47, p=0.001)(D1D; r=0.47, p=0.001). Conclusion: In the present study, phalangeal lengths of first digit in males showed a negligent correlation with stature. Rest of the phalangeal lengths in males showed significant correlation with stature. In females, all the phalangeal lengths showed significant correlation with stature and the values were higher in right hand phalangeal measurements than in left hand.